9(b+7)=9(b-5)

Simple and best practice solution for 9(b+7)=9(b-5) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9(b+7)=9(b-5) equation:


Simplifying
9(b + 7) = 9(b + -5)

Reorder the terms:
9(7 + b) = 9(b + -5)
(7 * 9 + b * 9) = 9(b + -5)
(63 + 9b) = 9(b + -5)

Reorder the terms:
63 + 9b = 9(-5 + b)
63 + 9b = (-5 * 9 + b * 9)
63 + 9b = (-45 + 9b)

Add '-9b' to each side of the equation.
63 + 9b + -9b = -45 + 9b + -9b

Combine like terms: 9b + -9b = 0
63 + 0 = -45 + 9b + -9b
63 = -45 + 9b + -9b

Combine like terms: 9b + -9b = 0
63 = -45 + 0
63 = -45

Solving
63 = -45

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| 1(23)(-18)(2)= | | Y-39=-39 | | 8k-4k-8= | | (1)(23)(-18)(2)= | | 2-6j+8j=-2j-10 | | 8y-8-3y=12y-6 | | -5(r+9)=-53 | | 9(o+2)=3(o-2) | | 5.7+1.8n=0.84 | | 5d=9d-20 | | 15k^2-8=-2k | | 8-6x+x=2-3x | | 9-5z=12-6z+7 | | 83-x=93-2x | | .8(x+4)-.3x=1.7 | | n*2-12=34 | | 3y-6y^2=0 | | 25=-7(x+5)+5x | | 5x+8y=6e | | 3x+5=350 | | 8=-4x+x+8 | | ln*(x+3)+ln*9=1 | | 8(x+9)=80 | | (-34)+50+50= | | 85-3x=4 | | -5n=13-13m | | 6x-2y=4x+6y | | y=2x^2-7x-30 | | 8x^2=4x+14 | | 6a+12=6a-12 | | p=8p+p | | -2y=14x-50 |

Equations solver categories